Implementation of Digital based Handover as an Effort to Improve Safety and Continuity of Patient Care - Susanti, Ni Luh Putu Dina; Wahyuningsih, Luh Gde Nita Sri; Parwati, Putu Atika; Jiyestha Aji Dharma Aryasa (Journal Of Nursing Practice, 2026)
Background: Digital-based handover systems have emerged as an innovative approach to standardize communication, support clinical decision-making, and enhance the integration of patient information across shifts and care units. Purpose: this study was to evaluate the implementation of a digital weighing system as an effort to improve safety and continuity of service for patients. Methods: This study used a non-experimental quantitative design with a cross-sectional approach. The sample for this study was the entire population, consisting of 220 respondents. Data collection was conducted using a standardized questionnaire with a Cronbach's alpha value of 0.88 and a Likert scale of 1–5. The data were then analyzed using descriptive statistics, normality tests, Pearson's correlation test, and simple/multiple linear regression to see the strength of the relationship and the contribution of independent variables to the dependent variable. Results: Base on result the implementation of digital weighing, the higher the safety and continuity of patient care. The r value is in the strong relationship category, indicating that the variables in this study have a strong relationship. Conclusion: The implementation of a digital-based handover system is not only a technological innovation, but also a strategic intervention in efforts to improve patient safety and continuity of service.